FINANCIAL FEASIBILITY OF PROPERTY TECHNOLOGY BUSINESS PLANNING (PROPTECH) AS AN ONLINE PROPERTY RENTAL SOLUTION - Sirait, Rizani Candra; Syah, Tantri Yanuar Rahmat; Negoro, Dimas Angga; Iskandar, Muhammad Dafi (Universitas Muhammadiyah Tangerang, 2025)
This study examines the financial planning strategy of a business in the property technology (PROPTECH) sector through a five-stage approach: financial goal setting, planning elements, financial projections, investment feasibility analysis, and financial performance evaluation. This plan aims to ensure financial sustainability and support the strategic and measurable development of PROPTECH's business. These stages involve managing income, expenses, and investments based on short-, medium-, and long-term projections. Analysis of ROI, NPV, IRR, and PP indicate strong investment feasibility, while evaluation of financial ratios such as liquidity, solvency, and profitability confirm PROPTECH's ability to manage capital effectively. The projection results show significant annual revenue growth, with profitability continuing to increase until the fifth year. Thus, this study provides a comprehensive framework to support business success in the PROPTECH sector through integrated financial management.